Association between prophylactic angiotensin-converting enzyme inhibitors and overall survival in Duchenne muscular dystrophy—analysis of registry data. (22nd March 2021) - Porcher, Raphaël; Desguerre, Isabelle; Amthor, Helge; Chabrol, Brigitte; Audic, Frédérique; Rivier, François; Isapof, Arnaud; Tiffreau, Vincent; Campana-Salort, Emmanuelle; Leturcq, France; Tuffery-Giraud, Sylvie; Ben Yaou, Rabah; et al.
Abstract: Aims: To estimate the effect of prophylactic angiotensin-converting enzyme inhibitors (ACEi) on survival in Duchenne muscular dystrophy (DMD). Methods and results: We analysed the data from the French multicentre DMD Heart Registry (ClinicalTrials.gov: NCT03443115). We estimated the association between the prophylactic prescription of ACEi and event-free survival in 668 patients aged 8 to 13 years, with normal left ventricular function, using (i) a Cox model with intervention as a time-dependent covariate, (ii) a propensity-based analysis comparing ACEi treatment vs. no treatment, and (iii) a set of sensitivity analyses. The study outcomes were overall survival and hospitalizations for heart failure (HF) or acute respiratory failure. Among the 668 patients included in the DMD Heart Registry, 576 (mean age 6.1 ± 2.8 years) were eligible for this study, of whom 390 were treated with ACEi prophylactically. Death occurred in 53 patients (13.5%) who were and 60 patients (32.3%) who were not treated prophylactically with ACEi, respectively. In a Cox model with intervention as a time-dependent variable, the hazard ratio (HR) associated with ACEi treatment was 0.49 [95% confidence interval (CI) 0.34–0.72] and 0.47 (95% CI 0.31–0.17) for overall mortality after adjustment for baseline variables. In the propensity-based analysis, 278 patients were included in the treatment group and 834 in the control group, with 18.5% and 30.4% 12-year estimated probability of death, respectively. ACEi were associated with a lower risk of death (HR 0.39; 95% CI 0.17–0.92) and hospitalization for HF (HR 0.16; 95% CI 0.04–0.62). All other sensitivity analyses yielded similar results. Conclusion: Prophylactic ACEi treatment in DMD was associated with a significantly higher overall survival and lower rates of hospitalization for HF. Graphical Abstract: